Old and new coins in Southern Hispania in the sixth century A.D - Mora-Serrano, Bartolomé (J. Chameroy, P.-M. Guihard, 2016)
The purpose of this paper is to analyse the behaviour of monetary circulation in Southern Hispania in the 6th century AD. During this time, there was a visible renewal of the monetary stock. This large quantitative increase contrasts with a shortage of information on coin circulation for the previous period, between the second quarter of the 5th century and the arrival of Byzantine authority in the Iberian Peninsula.
Keywords: Monedas romanas; Nummus; Late roman coins Hispania